Constructing 'reality': The portrayal of Internet child luring by Toronto-based newspapers 1998--2008 - Greco, Christopher A.P (University of Ottawa (Canada), 2009)
Often simplistic and misleading, the reporting of child sexual abuse has long been a staple of commercial news media's portrayal of crime and criminal justice. A mixed quantitative/qualitative content analysis methodology is applied to the study of three Toronto-based newspaper's construction of Internet Child Luring, between the 1st of January, 1998, and August 1st, 2008. Erected as a serious problem, above which a sober appraisal of known facts could sustain, a Textual Panic is said to exist within newsprint's rendering of the information-age crime. Rational cogitating offenders, undeterred by weak legislation and underfunded police forces, are described as exploiting the communication medium in attempts to lure defenseless children into illicit sexual activity.
Keywords: Journalism.; Sociology, Criminology and Penology.; Mass Communications.